A NaV1.8FlpO mouse enabling selective intersectional targeting of low threshold C fiber mechanoreceptors and nociceptors - Chen, John C. Y.; Kaczmarczyk, Lech; Jackson, Walker S.; Larsson, Max (Frontiers in Molecular Neuroscience, 2025)
Genetic targeting of select populations of cells in the mouse nervous system is often hampered by a lack of selectivity, as candidate genes for such targeting are commonly expressed by multiple cell populations, also in the same region. Intersectional targeting using two or more genes has been enabled by the development of reporter tools dependent on more than one recombinase or gene regulator. Still, widespread adoption of intersectional tools is complicated by a scarcity of driver mice expressing recombinases other than Cre. Here we report the generation and characterization of a new driver mouse that expresses the FlpO recombinase from the endogenous locus of the Scn10a gene encoding NaV1.8, a voltage-gated sodium channel that is almost exclusively expressed in the afferent limb of the peripheral nervous system. Moreover, among sensory neurons the channel is preferentially expressed in nociceptors and in low-threshold C-fiber mechanoreceptors (C-LTMRs). The mouse showed high recombination efficiency (97%) and selectivity (93%) in dorsal root ganglia. Reporter-expressing fibers were observed in a variety of peripheral tissues, including skin, skeletal muscle, genitalia, bladder and intestines. To validate the suitability of the FlpO mouse line for intersectional targeting, we crossed it with a mouse line expressing CreERT2 from the Th (tyrosine hydroxylase) locus. This approach resulted in strikingly selective and efficient targeting of C-LTMRs, showing robust visualization of nerve endings of these fibers in skin and spinal cord at the light and electron microscopic level. Thus, the NaV1.8Flpo mouse line presented here constitutes a selective and versatile tool for intersectional genetic targeting of NaV1.8 expressing primary afferent neurons.